Protective effects of alpha-lipoic acid on experimental sciatic nerve crush injury in rats: assessed with functional, molecular and electromicroscopic analyses. (1st December 2014) - Demir, Recep; Yayla, Muhammed; Akpinar, Erol; Cakir, Murtaza; Calikoglu, Cagatay; Ozel, Lutfu; Ozdemir, Gokhan; Mercantepe, Tolga
<x xml:space="preserve">Abstract</x> Aim: The present study aimed to demonstrate protective effects of alpha lipoic acid on experimental sciatic nerve crush injury model assessed with functional and electronmicroscopy analyses. Methods: In this study, groups were; Group 1; sham operated, Group 2; applied only sciatic nerve crush (Control), Group 3; Sciatic nerve crush + treated ALA 25 mg/kg (received orally) and Group 4; Sciatic nerve crush + treated ALA 50 mg/kg. Subsequently, sciatic nerves crush injury induced by forceps. At the second and fourth week, all animals were evaluated for sciatic functional index (SFI) and histomorphometric analyses with electronmicroscopy. Results: The SFI was significantly increased for both ALA-treated groups 30 days post-injury compared with control groups. The elecronmicroscopy results demonstrated that the axon diameter, the myelin diameter, the area of regenerating axon and miyelin were better in the treatment group than in the control group. Also ALA decreased IL-1β and Caspase 3 levels that increased in SNC group. Conclusions: These results suggest that ALA neuroprotective agent for peripheral nerve injury (PNI) and promoted peripheral nerve regeneration via its anti-inflammatory and antiapoptotic effects.